2017
DOI: 10.11604/pamj.2017.26.115.11471
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs prédictifs de l’adhésion médicamenteuse chez les patients en insuffisance cardiaque chronique: expérience marocaine

Abstract: L’adhésion médicamenteuse chez les patients ayant une insuffisance cardiaque chronique est reconnue comme l’un des problèmes majeurs dans la gestion de cette pathologie. L’état démographique et socioéconomique des pays africains peut avoir un impact sur l’adhésion au traitement de l’insuffisance cardiaque chronique. Nous avons réalisé une étude transversale de Septembre 2014 à Janvier 2015 portant sur les patients en insuffisance cardiaque chronique suivis au centre d’insuffisance cardiaque du département de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Unexpectedly, a higher level of depressive symptoms was significantly associated with a greater likelihood of dietary sodium adherence. In prior studies (Luyster et al, 2009;Ragbaoui et al, 2017), more severe depressive symptoms were associated with poorer medication adherence or dietary sodium adherence. These inconsistent findings may be due to differences in the measures.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Unexpectedly, a higher level of depressive symptoms was significantly associated with a greater likelihood of dietary sodium adherence. In prior studies (Luyster et al, 2009;Ragbaoui et al, 2017), more severe depressive symptoms were associated with poorer medication adherence or dietary sodium adherence. These inconsistent findings may be due to differences in the measures.…”
Section: Discussionmentioning
confidence: 83%
“…The findings imply that improvement in social support and consideration of education level and race can be important targets of interventions to improve medication adherence assessed by an objective measure. In a prior heart failure study (Ragbaoui et al, 2017), social support was also significantly associated with medication adherence assessed by a questionnaire. The findings of both studies demonstrate the important role of social support in medication adherence regardless of the measures.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…An observational study by Uchmanowicz9 using this scale found higher rates of adherence in participants with higher educational achievement and family support, indicating a possible relationship between socioeconomic factors and medication, albeit one that is not widely studied 10. Previous studies on medication adherence in elderly people in developing countries, especially in the context of polypharmacy, have previously incorporated socioeconomic variables.…”
Section: Introductionmentioning
confidence: 99%